KINERJA PENINGKATAN KESEJAHTERAAN ANGGOTA DAN KELUARGA STUDI DI DEWAN PENGURUS KORPRI KABUPATEN SLEMAN - Widhihadmoko, Kuncoro; Sugiyanto, Sugiyanto (Journal of Indonesian Rural and Regional Government, 2025)
This study aims to determine the performance of improving the welfare of KORPRI members and their families within the KORPRI Board of Directors in Sleman Regency, as mandated by the 8th KORPRI National Conference in 2015. The preamble to the KORPRI Articles of Association states that "to enhance the role of employees of the Republic of Indonesia to be more effective and efficient for the benefit of society, the nation, and the state, it is necessary to balance this with improving the welfare of KORPRI members and their families." This qualitative case study was conducted at the Technical Implementation Unit (UPTD) of the KORPRI Board of Directors Secretariat in Sleman Regency, Yogyakarta Special Region. Informants were selected using propurative sampling. Data were collected using observation, interviews, and documentation studies. Primary and secondary data were integrated in content analysis. Data validation was carried out in four stages: data entry, establishing validation rules, the validation process itself, and error handling. The results of the study indicate that the leadership and organizational culture of the UPTD Secretariat of the KORPRI Board of Directors in Sleman Regency are power-sharing organizations; this organization is a learning organization that consistently measures and evaluates its programs.